Judicial Protection of Women’s Maintenance Rights in Wife-Initiated Divorce: A Study of Religious Court Decisions in East Java - Wardana, Dwi Safira; bin Junoh, Muhammad Rasydan (Sakina: Journal of Family Studies, 2026)
Divorce has significant legal consequences, particularly regarding the rights and obligations of former spouses after the dissolution of marriage. One critical issue concerns women’s right to maintenance following divorce, especially in cases initiated by wives (cerai gugat), where judicial practice often shows varying outcomes. This study aims to analyze judges’ legal considerations in determining women’s maintenance rights in wife-initiated divorce cases and to examine the implementation of Supreme Court Regulation (PERMA) No. 3 of 2017 concerning Guidelines for Adjudicating Cases Involving Women in Conflict with the Law. This research employs normative legal research with a case approach. The data were obtained through the analysis of five Religious Court decisions: Pasuruan Number 0410/Pdt.G/2025/PA.Pas, Probolinggo Number 639/Pdt.G/2025/PA.Prob, Sidoarjo Number 3617/Pdt.G/2025/PA.Sda, Surabaya Number 4099/Pdt.G/2025/PA.Sby, and Malang Number 51/Pdt.G/2025/PA.Mlg. The findings indicate that judges’ considerations in determining women’s maintenance rights are influenced by several factors, including the causes of divorce, the parties’ economic conditions, the wife’s contributions during the marriage, and the application of women’s protection principles as regulated in PERMA No. 3 of 2017. The study further reveals that some judges adopt a substantive justice approach by granting maintenance rights despite the divorce being initiated by the wife. The novelty of this research lies in its comparative analysis of court decisions, which identifies patterns of inconsistency as well as a gradual shift toward gender-sensitive judicial reasoning. This study contributes to formulating ideal standards of legal reasoning for judges and emphasizes the importance of integrating gender perspectives in ensuring effective protection of women’s post-divorce maintenance rights. <!–a=1–><!–a=1–>